STIGMATIZING CONTENT ON SOCIAL MEDIA AND ATTITUDE OF UNIVERSITY STUDENTS: ANALYSIS OF MENTAL HEALTH STIGMA - Taufiqnur Selamat; Azlina Abu Bakar; Mohd Muslim Md Zalli; Mohd Syaubari Othman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Stigma in mental illness happens when someone has an unfair attitude or belief about a person with mental health challenges that causes social isolation, social discrediting and reduced likelihood of staying with treatment. The objective of this study is to see the influence of attitude factors and the effect of social media on stigma towards mental patients among public university students. A total of 350 students around the Klang Valley were involved in this study through simple random sampling. The questionnaires used are Stigma and Self-Stigma Scales (SASS), Community Attitude Towards Mental Illness (CAMI) scale and Effects of Social Media Use on Perception on Mental Illness (ESMUPMI). The findings of the study show that the majority of students show a high level of stigma towards mental patients (65%), medium (24%) and low (11%). This study also found that the majority (84%) of students agreed that social media was their main source of information about mental problems; believe that social media sharing about mental illness is accurate (71%) and believe that social media is influential in changing someone’s opinion or perception of this issue. In addition, the findings also show that attitudes and social media affect stigma against mental patients (β=0.276 & β=0.157,p<0.01) and the R2 value is 0.206. Therefore, all hypotheses were accepted. On top of that, the government and institutions need to take steps to control the issue of stigma against mental patients in the community considering that mental illness has become the second highest disease in Malaysia since 2020.